IMPACT OF DIFFERENTIAL BIOFEEDBACK INTERVENTIONS ON AUTONOMIC HABITUATION AND FATIGABILITY IN SOCCER PLAYERS - SAHA SRILEKHA; AHMED MARUF; HUDA FOUJIA; NURFARAH EZZATY BINTI MOHD ZAHIR; IBRAHIM NUR FASYA; SAHA, SOUMENDRA (International Journal of Pharma and Bio Sciences, 2015)
Purpose of this study was to identify and compare the efficacy of skin conductance (Sc) and electromyography (EMG) biofeedback intervention techniques in regulation of sudomotor nerve activity (SNA) and maximal voluntary contraction (MVC) evident in high-performing soccer players having dismal performance. All of the players were assessed with autonomic measures of emotionality (SNA and Sc amplitude); electromyography evaluation of MVC. Fifty-four National-selection group soccer players in Malaysia were randomly categorized into three groups (Gr. A, N = 18, no-intervention control group); Gr. B (who received EMG biofeedback training) and Gr. C (received Sc biofeedback intervention). Players in the intervention groups received their respective trainings for 12 weeks (15 min.s /day for 3 days/ week). Post-intervention analyses revealed marked improvement in the bilateral shooting performance of the soccer players who received Sc and EMG biofeedback intervention training, which were capable of modulating autonomic indices of emotionality as well as the muscle potentiality in the form of enhanced maximal voluntary contraction in the players.